Structure and magnetic properties of superparamagnetic ferrite nanoparticles. (November 2019) - Farheen, Atiya; Singh, Rajender
Abstract: Superparamagnetic Mn-Zn ferrite nanoparticles have been emerging as an important material due to its potential application in the preparation of stable ferrofluids. The superparamagnetic ferrite nanoparticles were prepared through co-precipitation method. The Rietveld refinement of X-ray diffraction confirms the cubic spinel structure with fd-3m space group. The average crystallite size of the nanoparticles observed from X-ray diffraction is ∼5nm. The transmission electron microscope micrographs also confirm the nano phase of the Mn-Zn ferrite nanoparticles. The s-shape of the magnetic hysteresis loop indicates the superparamagnetic behaviour of the nanoparticles. The narrow electron paramagnetic resonance (EPR) spectra also confirm the superparamagnetic nature of the nanoparticles.